Governance, urbanization, and pollution: A cross-country analysis of global south region - Devi Prasad Dash; Smruti Ranjan Behera; D. Tripati Rao; Narayan Sethi; Nanthakumar Loganathan (Cogent Economics & Finance, 2020)
This paper investigates the impact urbanization, industrialization, corruption, human development, energy consumption, and foreign direct investment (FDI) on carbon dioxide (CO2) emissions of 61 developing economies of the global south region of Asia, Africa, and Latin America during the period 1990-2015. The empirical results show that the effect of corruption on CO2 emissions is indeed heterogeneous and contradictory. Specifically, results exhibit that due to immature economic system, and policy paralysis, corruption penetrates the developing economies, and eventually cause carbon emission and pollution. Furthermore, results reveal that FDI guided by clean development mechanism and involved in emission reduction projects in the developing economies play a predominant role to curb the CO2 emission, pollution, and environmental degradation.
Keywords: D73; O18; Q53; O15; 330; Corruption; governance; pollution; urbanization; human development